2007
DOI: 10.1111/j.1469-8749.2005.tb01101.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in idiopathic generalized epilepsy of childhood

Abstract: This study evaluated the cognitive profiles of children with idiopathic generalized epilepsy (IGE), uniformly treated with valproic acid with well-controlled seizures. Twenty-four were neuropsychologically evaluated. They comprised: 14 females, 10 males: 12 with generalized tonic-clonic seizures (GTCS), mean age 14y 4mo, SD 1y 7mo, range 12y to 16y 4 mo; 12 with absence seizures (AS) mean age 14y 5mo, SD 1y 10mo, range 11y to 16y 4mo, with intellectual abilities within the normal range and age-appropriate scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…The lateral dorsal and anterior nuclei of the thalamus project directly to the posterior cingulate as part of the Papez memory circuit [4]. The cognitive profiles of children with IGE showed significantly poorer performance in attention, verbal learning and memory, although these children had normal intelligence and their seizures were well controlled with valproic acid [20]. The rCBF of anterior cingulate was also decreased in the present study.…”
Section: ■ Decreased Rcbf In Thalamus and Cingulate Gyrusmentioning
confidence: 87%
See 1 more Smart Citation
“…The lateral dorsal and anterior nuclei of the thalamus project directly to the posterior cingulate as part of the Papez memory circuit [4]. The cognitive profiles of children with IGE showed significantly poorer performance in attention, verbal learning and memory, although these children had normal intelligence and their seizures were well controlled with valproic acid [20]. The rCBF of anterior cingulate was also decreased in the present study.…”
Section: ■ Decreased Rcbf In Thalamus and Cingulate Gyrusmentioning
confidence: 87%
“…All patients and healthy volunteers were right-handed. The mean age of the patients at the time of SPECT scanning was 21.3 ± 2.7 years (16-35) and their mean age at the onset of epilepsy was 17.3 ± 2.5 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years.…”
Section: ■ Clinical Informationmentioning
confidence: 99%
“…More interestingly, after 20 weeks of AED treatment, when patients were seizure free, attention deficits were still present, suggesting that these deficits might have little to do with the seizures themselves. An earlier study also reported deficits in verbal and non-verbal attention (Henkin et al, 2005). GAERS, which were never exposed to any drug before 5-CSRTT testing, had no marked attention deficit.…”
Section: Necsmentioning
confidence: 92%
“…Even if this type of epilepsy is classified as benign in humans, reports mention cognitive, language and behavioral/emotional problems in children. Notably, difficulties have been identified in sustained visual attention (Levav et al, 2002), visual spatial skills (Pavone et al, 2001), and both verbal and non-verbal attention (Henkin et al, 2005). In one study, verbal memory was impaired compared to intact non-verbal memory (Henkin et al, 2005), whereas in others, dysfunctions were reported in non-verbal memory and delayed recall, but not in verbal memory (Jambaqué et al, 1993;Pavone et al, 2001).…”
Section: Introductionmentioning
confidence: 97%
“…Although CAE was originally considered a benign disorder (Dieterich et al, 1985), recent research has shown that children with absence epilepsy have co-morbid behavioral (Caplan et al, 2009) and cognitive (Caplan et al, 2009;Henkin et al, 2005;Killory et al, 2011;Loughman et al, 2014;Mandelbaum & Burack, 1997;Pavone et al, 2001) symptoms. In particular, visual skill and visual memory deficits are consistently observed in CAE (Nolan et al, 2004;Pavone et al, 2001;Siren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%